Landscape Architecture Processes and Practices Towards Sustainable Development - Loures, Luís; Ergen, Mustafa (IntechOpen, 2021)
This book highlights the diverse nature of the scientific domains associated with landscape architecture. It emphasises the need to acknowledge that the contribution of each research domain is equally important, offering complementary development opportunities while enabling landscapes to fulfill their multiple functions and ecosystem services in an integrated way, underlining the relevance of theory, methods, and practice to promote sustainable landscape planning and design.